1989
DOI: 10.1093/nar/17.23.10083
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and proposed secondary structure ofColumnealatent viroid: a natural mosaic of viroid sequences

Abstract: The Columnea latent viroid (CLV) occurs latently in certain Columnea erythrophae plants grown commercially. In potato and tomato, CLV causes potato spindle tuber viroid (PSTV)-like symptoms. Its nucleotide sequence and proposed secondary structure reveal that CLV consists of a single-stranded circular RNA of 370 nucleotides which can assume a rod-like structure with extensive base-pairing characteristic of all known viroids. The electrophoretic mobility of circular CLV under nondenaturing conditions suggests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 28 publications
3
62
0
1
Order By: Relevance
“…CLVd, for example, is mostly a mosaic of viroid sequences known from other viroids. Its left and right terminal domains are essentially identical with those of Pospiviroids, whereas its CCR is identical with that of HSVd (22). Thus, placement of CLVd with one of these groups depends on what one considers as the most important criteria for classification.…”
Section: Phylogenetic Methodsmentioning
confidence: 99%
“…CLVd, for example, is mostly a mosaic of viroid sequences known from other viroids. Its left and right terminal domains are essentially identical with those of Pospiviroids, whereas its CCR is identical with that of HSVd (22). Thus, placement of CLVd with one of these groups depends on what one considers as the most important criteria for classification.…”
Section: Phylogenetic Methodsmentioning
confidence: 99%
“…Furthermore, one of the critical loops for PSTVd trafficking has also been mapped to this domain (Zhong et al, 2008). Unlike the T L and T R domains, the P domain has not been associated with the contribution of the origin of new viroids (divergence) by molecular recombinant or rearrangement processes (Haseloff et al, 1982;Diener, 1983;Keese & Symons, 1985;Hammond et al, 1989;Szychowski et al, 2005;Darò s et al, 2006). Therefore, the functional role of…”
Section: Discussionmentioning
confidence: 99%
“…The adjective ''polythetic'' means that the viruses (or viroids) do not need to exhibit a common core set of biological, genetic or structural properties, but rather that their properties overlap to varying degrees. As discussed below, this definition provides a useful framework in which to consider the classification of columnea latent viroid (CLVd, [31] and dahlia latent viroid, DLVd, [63]), two viroids whose CCRs most closely resemble that of HSVd but also, like PSTVd, contain a TCR (see below).…”
Section: Criteria For Viroid Species Demarcationmentioning
confidence: 99%
“…Pairwise sequence comparisons strongly suggested that the terminal domains of certain pospiviroids such as tomato apical stunt viroid (TASVd) and TPMVd have undergone recombination in vivo, most likely as the result of discontinuous transcription by the RNA polymerase II involved in viroid replication. On the other hand, the genesis of several viroids, including CLVd [31] and Australian grapevine viroid (AGVd, [52]), was proposed to result from recombination events between viroids belonging to species of different genera co-infecting the same host. Internal recombination events within the same viroid, generating terminal repeats, have also been reported for some nuclear-replicating viroids, such as coconut cadang-cadang viroid (CCCVd) and CEVd [14,32,57].…”
Section: Recombinant Viroidsmentioning
confidence: 99%
See 1 more Smart Citation